From early lessons to new frontiers: the worm as a treasure trove of small RNA biology - Youngman, Elaine M.; Claycomb, Julie M. (Frontiers in Genetics, 2014)
In the past twenty years, the tiny soil nematode C. elegans has provided critical insights into our understanding of the breadth of small RNA-mediated gene regulatory activities. The first microRNA was identified in C. elegans in 1993, and the understanding that dsRNA was the driving force behind RNA-mediated gene silencing came from experiments performed in C. elegans in 1998. Likewise, early genetic screens in C. elegans for factors involved in RNAi pointed to conserved mechanisms for small RNA-mediated gene silencing pathways, placing the worm squarely among the founding fathers of a now extensive field of molecular biology. Today, the worm continues to be at the forefront of ground-breaking insight into small RNA-mediated biology. Recent studies have revealed with increasing mechanistic clarity that C. elegans possesses an extensive nuclear small RNA regulatory network that encompasses not only gene silencing but also gene activating roles. Further, a portrait is emerging whereby small RNA pathways play key roles in integrating responses to environmental stimuli and transmitting epigenetic information about such responses from one generation to the next. Here we discuss endogenous small RNA pathways in C. elegans and the insight worm biology has provided into the mechanisms employed by these pathways. We touch on the increasingly spectacular diversity of small RNA biogenesis and function, and discuss the relevance of lessons learned in the worm for human biology.